Recovery of the Spanish nationality RDGRN [11ª] 30 September 2019 [born in Argentina - Vargas Gómez-Urrutia, Marina (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
Once Spanish nationality is lost, there is a possibility of recovering it. To do so, it is necessary to meet the following requirements: The interested party must be legally resident in Spain. However, this requirement shall not apply to emigrants or the children of emigrants (art. 26 Civil Code). This commentary analyzes a resolution of the DGRN on the recovery of Spanish nationality. The peculiarity of the case lies in the intention of the promoter to expand the concept of emigrant-children of emigrant of article 26 of the Civil Code to a very peculiar case of a back and forth emigration. An extension of the criterion that the DGRN does not consider acceptable.
Keywords: Spanish nationality, lost and recovering; requirements, legal resident; not apply to emigrants or the children of emigrants (art. 26 Civil Code)